Implementation of Tanjung Lesung Tourism Development Policy as a Special Economic Zone (Sez) in Pandeglang Regency - Supriatno, Eko; Implementation, Policy (CV. Lenggogeni Data Publishing, 2023)
This study aims to analyze the implementation of the tourism development policy of Tanjung Lesung as a Special Economic Zone (SEZ) in Pandeglang Regency and to identify its supporting and inhibiting factors. The study applies a descriptive qualitative approach using interviews, observations, and documentation as data collection techniques. The findings indicate that the implementation of the Tanjung Lesung SEZ policy has not been fully effective. The main constraints include limited public understanding of policy objectives, inadequate infrastructure and human resources, and weak coordination among central, regional, and private stakeholders. Additionally, the absence of a clear Standard Operating Procedure (SOP) hinders program consistency. To improve effectiveness, the study recommends establishing detailed SOPs, strengthening intergovernmental coordination, and involving local communities and private sectors more actively in the planning and implementation processes of Tanjung Lesung’s SEZ development.